Evaluating Instrument Quality: Rasch Model – Analyses of Post Test of Curriculum 2013 Training - Komalasari (FKIP Universitas Palangka Raya, 2018)
The main purpose of this study was to evaluate the quality of post test utilized by LPMP Central Kalimantan Indonesia in curriculum 2013 training for X grade teachers. It uses Rasch analysis to explore the item fit, the reliability ( item and person), item difficulty, and the Wrigh map of post test. This study also applies Classical Test Teory (CTT) to determine item discrimination and distracters. Following a series of iterative Rasch analyses that adopted the “data should fit the model” approach, 30 items post test of curriculum 2013 training was analyzed using Acer Conquest 4 software, software based on Rasch measurement model. All items of post test of curriculum 2013 training are sufficient fit to the Rasch model. The difficulty levels (i.e. item measures) for the 30 items range from –1.746 logits to +1.861 logits. The item separation reliability is acceptable at 0.990 and person separation reliability is low at 0.485. The wright map indicates that the test is difficult for the teachers or the teachers have low ability in knowledge of curriculum 2013. The post test items cannot cover all the ranges of the teachers’ ability levels. Items discrimination of post test of curriculum 2013 training grouped into fair discrimination (item 2, 4, 5, 8, 11, 18) and poor discrimination (1, 3, 6, 7, 9, 10,12, 13, 14, 15, 16, 17, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30). Some distracters from item 1, 2, 6, 7, 8, 9, 11, 13, 16, 17, 18, 19, 20, 22, 24, 25, 27, 28, 29 and 30 are problematic. These distracters require further investigation or revision.